Morphological, nutraceutical and sensorial properties of cultivated Fragaria vesca L. berries: influence of genotype, plant age, fertilization treatment on the overall fruit quality - Del Bubba, Massimo; Giordani, Edgardo; Ancillotti, Claudia; Petrucci, William Antonio; Ciofi, Lorenzo; Morelli, Daniele; Marinelli, Cristian; Checchini, Leonardo; Furlanetto, Sandra (Agricultural and Food Science, 2016)
Sucrose, glucose, fructose, citric, malic, ascorbic (AA) and dehydroascorbic (DHAA) acids, total polyphenols (TP), radical scavenging activity (RSA), physicochemical and sensorial properties were determined on F. vesca Alpine (ALP) and Regina delle Valli (RDV) berries in relation to plant age and fertilisation treatment (Effective Microorganism Technology, EMT vs. traditional fertilization, TFT). ALP berries had a sum of AA and DHAA about 20% lower and TPs about 30% higher than RDV. Plant age affected most physicochemical parameters, sugars and organic acids, as well as sensorial appreciation, being them generally higher in berries produced in the second year. TPs were not affected by plant age. EMT produced an increase of 50%, 70% and 20% for TP, organic acids and RSA, respectively. Although changes in berry quality are expected with plant age, EMT cultivation of ALP should be preferred to the growth of RDV under TFT, to obtain fruits more valuable from the nutraceutical viewpoint.